Enhanced Storage Mechanism for Secured Parallel Network File System - K J, Latesh Kumar (2018)
The main aim of this dissertation is to study how parallel network file system and storage appliances are integrated to storage computing. The prime focus is on file locking techniques, state maintenance of file locks and layouts, data compression and data protection across network attached storage and parallel network file system. The problem statement relies how the enhancement of storage mechanism for secured parallel network file system will benefit the storage computing environment. In order to comply with these objectives, a study is conducted and data is collated by visiting storage customer data sites, references of storage summit articles, journal references and by participating in storage conferences and workshops across globe. Based on the analysis of data, the legacy usage of network lock manager and network status monitor in file locking mechanism, unhandled locks and layouts, legacy security model used with pNFS client and servers, a single pattern of file-based data compression and non-dynamic external data protection techniques on storage computing system has resulted high impact on network attached storage computing. The challenges faced translates how the new techniques, lease and delegation algorithm for file locking, snapshot enabled locks and layouts for data state, integration of highly secured Kerberos security on storage for pNFS locks and layouts, data block size algorithm enabled deduplication on file, block and object patterns and the redundant array of independent disk data protection can create impact on storage computing system. The proposed techniques resulted synchronous LEASE file locking, capturing of state of locks and layouts, Kerberos secured the pNFS locks and layouts on storage, new algorithm enabled the scalable data compression using data block size compression algorithm and better dynamic data protection using RAID.